Fluid mechanics for engineers - Chin, David A. (Boston : Pearson, 2017)
'This is a textbook for a first course in fluid mechanics taken by engineering students.The unique features of this textbook are that it: (1) focuses on the basic principles fluid mechanics that engineering students are likely to apply in their subsequent required undergraduate coursework, (2) presents the material in a rigorous fashion, and (3) provides many quantitative examples and illustrations of fluid mechanics applications. Students in all engineering disciplines where fluid mechanics is a core course should find this textbook stimulating and useful. In some chapters, the nature of the material necessitates a bias towards practical applications in certain engineering disciplines, and the disciplinary area of the author also contributes to the selection and presentation of practical examples throughout the text. In this latter respect, practical examples related to civil engineering applications are particularly prevalent'--
Properties of fluids -- Fluid statics -- Kinematics and streamline dynamics -- Finite control volume analysis -- Differential analysis -- Dimensional analysis and similitude -- Flow in closed conduits -- Turbomachines -- Flow in open channels -- Drag and lift -- Boundary-layer flow -- Compressible flow.
Includes bibliographical references and index.
Keywords: Fluid mechanics -- Textbooks